PENERAPAN TEORI KEMANFAATAN HUKUM (UTILITARIANISME) DALAM KEBIJAKAN PEMBATASAN USIA PERNIKAHAN - Ainullah Ainullah (LP2M IAI Miftahul Ulum Pamekasan, 2017)
After the revision of Law No.1 of 1974 to Law No.16 of 2019, the minimum age for marriage has changed to 19 years for both men and women. Of course, this change is filled with pros and cons. There are those who have too high a viewpoint and can fertilize an under-handed marriage (sirri), others have a less high opinion because the age of maturity is no longer at the age of 19 years. By starting from the phenomenon of the current age limitation discourse, the author wants to examine in depth the policy by using the theory of legal utility of utilitarianism in legal philosophy as a test material. Utilitarianism is one of the schools of legal philosophy initiated by Jeremy Bentham. According to Bentham, the purpose of law is to provide the greatest benefit and happiness to as many members of the community as possible. So, the concept puts benefit as the main goal of law. The measure is the greatest happiness for as many people as possible. The assessment of whether this law is good or bad, fair or not really depends on whether the law is able to give happiness to humans or not. Benefit is defined as happiness (happiness). The conclusion is that the policy relevance of limiting the age of marriage as stipulated in Law no. 16 of 2019 with the principle of benefit in the philosophy of utilitarianism is closely related. This is because the policy does not want to hamper someone's desire to get married. But the restriction rests on the reason that entering the world of marriage requires maturity and mental maturity. This can only be done if the government sets a age limit for men and women to marry.